The role of composition in the interpretation of the Rider on the white horse and the seven seals in Revelation - De Villiers, Pieter G. R. (HTS teologiese studies, 2004)
The article investigates the way in which the author of Revelation composed the seven seals: Formal elements group the seals in smaller patterns. It then explains how this reading of the composition contributes to the process of interpretation by analysing the Rider on the white horse as first seal. Other aspects of the author’s compositional skills are brought into discussion in a last part of the article where the meaning of the Rider on the white horse and the ambiguity of the symbols are discussed.